2021
DOI: 10.1073/pnas.2106868118
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the hypothalamic–pituitary–adrenal axis by exogenous and endogenous GDF15

Abstract: An acute increase in the circulating concentration of glucocorticoid hormones is essential for the survival of severe somatic stresses. Circulating concentrations of GDF15, a hormone that acts in the brain to reduce food intake, are frequently elevated in stressful states. We now report that GDF15 potently activates the hypothalamic–pituitary–adrenal (HPA) axis in mice and rats. A blocking antibody to the GDNF-family receptor α-like receptor completely prevented the corticosterone response to GDF15 administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 71 publications
3
38
0
2
Order By: Relevance
“…This suggests that GDF15 might be effective to induce stress and anxiety. This fits with recent observations in rodent models that exogenous GDF15 application as well as activation of endogenous GDF15 by genotoxic or endoplasmic reticulum toxins led to an activation of the hypothalamic–pituitary–adrenal (HPA) stress axis, which was absent in GDF15 −/− [ 50 ]. In a mouse model of GDF15 induction as a myomitokine, we could show that endogenous activation of the GDF15–GFRAL pathway leads to increased anxiety related behavior and induces a day-time restricted anorexia by increased hypothalamic corticotropin releasing hormone (CRH) acting via CRH receptor 1 [ 51 ].…”
Section: Gdf15 As a Myokine—signaling And Physiological Significancesupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that GDF15 might be effective to induce stress and anxiety. This fits with recent observations in rodent models that exogenous GDF15 application as well as activation of endogenous GDF15 by genotoxic or endoplasmic reticulum toxins led to an activation of the hypothalamic–pituitary–adrenal (HPA) stress axis, which was absent in GDF15 −/− [ 50 ]. In a mouse model of GDF15 induction as a myomitokine, we could show that endogenous activation of the GDF15–GFRAL pathway leads to increased anxiety related behavior and induces a day-time restricted anorexia by increased hypothalamic corticotropin releasing hormone (CRH) acting via CRH receptor 1 [ 51 ].…”
Section: Gdf15 As a Myokine—signaling And Physiological Significancesupporting
confidence: 91%
“…A recent publication reported that GDF15 activates the HPA axis, resulting in increased circulating glucocorticoids (corticosterone in rodents, cortisol in humans) [ 50 ]. One of the key functions of corticosterone/cortisol is to increase blood glucose levels by increasing hepatic glucose output.…”
Section: Gdf15 As a Myokine—signaling And Physiological Significancementioning
confidence: 99%
“…While our data clearly support the notion of an induction of hypothalamic CRH by GDF15-GFRAL signaling, our mouse model of chronic elevated GDF15 shows that chronic activation of the GDF15-GFRAL pathway might increase stress susceptibility but does not induce a sustained increase of corticosterone levels. Importantly, while acute administration of recombinant GDF15 promotes supraphysiological plasma GDF15 levels of >30ng/ml after 1-hr and >10ng/ml 4-hrs post -treatment in mice 38 , circulating GDF15 levels in TG mice oscillate in a range of 0.35 -1.4ng/ml (Fig. 1b,d) in a circadian manner.…”
Section: Mainmentioning
confidence: 92%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted September 24, 2021. ; https://doi.org/10.1101/2021.09.22.461199 doi: bioRxiv preprint 8 chronic elevated GDF15 shows that chronic activation of the GDF15-GFRAL pathway might increase stress susceptibility but does not induce a sustained increase of corticosterone levels. Importantly, while acute administration of recombinant GDF15 promotes supraphysiological plasma GDF15 levels of >30ng/ml after 1-hr and >10ng/ml 4-hrs post -treatment in mice 38 , circulating GDF15 levels in TG mice oscillate in a range of 0.35 -1.4ng/ml (Fig. 1b,d) in a circadian manner.…”
Section: Mainmentioning
confidence: 92%
See 1 more Smart Citation